Defluorinative Asymmetric Allylic Alkylations - Rodríguez, Paula; Duran, Jordi; Gisbert, Martí; Companyó, Xavier (Synlett, 2024)
The introduction of allyl fluorides as alternative electrophiles in asymmetric allylic alkylation reactions has recently attracted significant interest. Despite the intrinsic thermodynamically demanding C–F bond-cleavage event, the fluorophilic nature of the silicon atom is key in assisting the activation and cleavage of the allylic C–F bond. Thus, the use of silylated compounds as unconventional nucleophiles, together with the Lewis basicity of fluorine when acting as a leaving group, enables the development of innovative chemical transformations within mild and selective catalytic schemes. This Synpacts article summarizes the diverse defluorinative asymmetric allylic alkylations with allyl fluorides reported to date under both chiral Lewis base and transition-metal catalysis.
Keywords: C–F bond activation; defluorination; asymmetric catalysis; allylic alkylation; Lewis base catalysis; transition-metal catalysis